Integrating toxicity reduction strategies for materials and components into product design: A case study on utility meters. (21st February 2013) - Lam, Carl W; Lim, Seong‐Rin; Ogunseitan, Oladele A; Shapiro, Andrew A; Saphores, Jean‐Daniel M; Brock, Andrew; Schoenung, Julie M
Abstract: Using RIO Tronics utility meter products as an industrial case study, the numeric Fraunhofer Toxic Potential Indicator (TPI) assessment tool is used to determine high impact materials with the aim of reducing the content of inherently toxic substances in these products. However, because product redesign with alternative materials affects entire components, overall component toxicity potential must also be explored. To achieve this, material TPI scores are aggregated into component TPI scores by 2 methods: 1) the Sum‐Weighted Component TPI method, which considers the mass of materials in the component to assign an overall score, and 2) the Max Component TPI method, which scores the component with the highest impact material. With consideration of uncertainties from materials' toxicity information and mass estimates, key results from both scoring methods prioritized components that contain acrylonitrile‐based polymers, polyvinyl chloride (PVC), and stainless steel. Furthermore, an alternative materials assessment is carried out to identify less‐toxic substitutes to meet cost and technical constraints. Substitute materials such as Al alloys for stainless steel and high‐density polyethylene for PVC show promise for a combination of toxicity reduction and cost‐effectiveness. The new screening methodology described can help product designers systematically benchmark toxicity potential in parallel to cost and functionality. Integr Environ Assess Manag 2013; 9: 319–328. © 2012 SETAC